Effects of traffic control on the soil physical quality and the cultivation of sugarcane - Souza, Gustavo Soares De; Souza, Zigomar Menezes De; Silva, Reginaldo Barboza da [UNESP]; Barbosa, Ronny Sobreira [UNESP]; Araújo, Fernando Silva (Sociedade Brasileira de Ciência do Solo, 2014)
The cultivation of sugarcane with intensive use of machinery, especially for harvest, induces soil compaction, affecting the crop development. The control of agricultural traffic is an alternative of management in the sector, with a view to preserve the soil physical quality, resulting in increased sugarcane root growth, productivity and technological quality. The objective of this study was to evaluate the physical quality of an Oxisol with and without control traffic and the resulting effects on sugarcane root development, productivity and technological quality. The following managements were tested: no traffic control (NTC), traffic control consisting of an adjustment of the track width of the tractor and sugarcane trailer (TC1) and traffic control consisting of an adjustment of the track width of the tractor and trailer and use of an autopilot (TC2). Soil samples were collected (layers 0.00-0.10; 0.10-0.20 and 0.20-0.30 m) in the plant rows, inter-row center and seedbed region, 0.30 m away from the plant row. The productivity was measured with a specific weighing scale. The technological variables of sugarcane were measured in each plot. Soil cores were collected to analyze the root system. In TC2, the soil bulk density and compaction degree were lowest and total porosity and macroporosity highest in the plant row. Soil penetration resistance in the plant row, was less than 2 MPa in TC1 and TC2. Soil aggregation and total organic carbon did not differ between the management systems. The root surface and volume were increased in TC1 and TC2, with higher productivity and sugar yield than under NTC. The sugarcane variables did not differ between the managements. The soil physical quality in the plant row was preserved under management TC1 and TC2, with an improved root development and increases of 18.72 and 20.29 % in productivity and sugar yield, respectively.

O cultivo do canavial com uso intenso de máquinas, principalmente na colheita, resulta na compactação do solo, o que influencia no desenvolvimento da cultura. O manejo com controle de tráfego agrícola representa uma alternativa ao setor, podendo preservar a qualidade física do solo, resultando em maior crescimento radicular, produtividade e qualidade da cana. Objetivou-se com este trabalho avaliar a qualidade física de um Latossolo Vermelho com e sem controle de tráfego agrícola e seu efeito no desenvolvimento radicular, na produtividade e na qualidade tecnológica da cana-de-açúcar. Os manejos avaliados foram: testemunha sem controle de tráfego (NTC), controle de tráfego com ajuste da bitola do trator e do transbordo de cana colhida (TC1) e controle de tráfego com ajuste da bitola e uso de piloto automático (TC2). Amostras de solo foram coletadas nas camadas 0,00-0,10; 0,10-0,20; e 0,20-0,30 m nas linhas de plantio e do rodado (entrelinha) e na região do canteiro, distante 0,30 m da linha de plantio. A produtividade foi medida com balança específica para transbordo. As variáveis tecnológicas da cana foram medidas em cada parcela. Os monólitos de solo foram coletados para análise do sistema radicular. O TC2 apresentou menor densidade e grau de compactação e maior porosidade total e macroporosidade na linha de plantio. A resistência do solo à penetração, na linha de plantio, foi inferior a 2 MPa no TC1 e no TC2. Os sistemas de manejo não diferiram quanto à agregação do solo e ao carbono orgânico total. Os manejos TC1 e TC2 apresentaram maior superfície e volume radicular, com maior produtividade e rendimento de açúcar em relação ao manejo NTC. As variáveis tecnológicas da cana não diferiram entre os manejos. Os manejos TC1 e TC2 preservaram a qualidade física do solo na região da soqueira, aumentando o desenvolvimento radicular, com incremento de 18,72 e 20,29 % na produtividade de cana e no rendimento de açúcar, respectivamente.
Controle de tráfego e seu efeito na qualidade física do solo e no cultivo da cana-de-açúcar
Keywords: mecanização agrícola; compactação do solo; sistema radicular; qualidade tecnológica; Saccharum sp; agricultural mechanization; soil compaction; root system; technological variables; Saccharum sp